Polymorphisms of IL-4 Gene in Iraqi Behçet’s Disease Pat - Israa Harjan Mohsen (Journal of Global Pharma Technology, 2016)
The present research was carried out to reveal the correlation of IL-4 gene polymorphisms with Iraqi Behçet’s Disease patients. The technique that used in the present study is PCR-SSCP technique. DNA was extracted from blood. The results show that there was strong association between IL-4 gene and Behçet’s Disease there were two patterns (A and B), polymorphisms show significant differences(p>0.05) between patients and control where pattern (A) was occurred with percentage (2%) and (39%) while in the control and patients respectively .The pattern (B) was occurred with percentage (98% ) and (61%)  in the control and patients respectively .The results concluded that IL-4 gene polymorphisms were involved in  pathogenesis of Behçet’s Disease , our finding require more exploration to use this result as early hint of Behçet’s Disease  prevalence.Keywords: IL-4 .PCR-SSCP technique, Haplotypes, Polymorphisms, Behçet’s Disease